Comesa and Sadc : Prospects and Challenges for Regional Trade Integration - Khandelwal, Padamja (IMF Working Papers; Working Paper ;, 2004)
Regional integration has been seen in Africa as a means of encouraging trade and securing economies of scale. This paper examines in detail the prospects and challenges for trade expansion in the two most prominent arrangements in eastern and southern Africa: the Common Market for Eastern and Southern Africa (COMESA) and the Southern African Development Community (SADC). It finds that possibilities of growth in intraregional trade may be limited, but that the two arrangements offer opportunities for member countries to gain policy credibility for trade reforms and tariff liberalization and to address structural weaknesses. In this regard, the negotiation of the Economic Partnership Agreements with the European Union can also have a significant impact.